The role of maternally transferred antibodies in maternal performance in red deer - Julie Gauzere; Craig A. Walling; Joel L. Pick; Kathryn Watt; Penny Jack; Alison Morris; Sean Morris; Josephine M. Pemberton (Ecology Letters, 2021)
Maternal effects are ubiquitous. Yet, the pathways through which maternal effects occur in wild mammals remain largely unknown. We hypothesise that maternal immune transfer is a key mechanism by which mothers can affect their offspring fitness, and that individual variation in maternally derived antibodies mainly depends on a mother's characteristics and the environmental conditions she experiences. To test this, we assayed six colostrum‐derived antibodies in the plasma of 1447 neonates in a wild red deer population. Neonatal antibody levels were mainly affected by maternal genes, environmental variation and costs of prior reproductive investment. We found consistent heterogeneity in maternal performance across traits, with mothers producing the heaviest calves also having calves with more antibodies. Unexpectedly, antibody levels were not associated with calf survival. We provide a unique example of how evolutionary theory on maternal effects can be used to gain insight into the causes of maternal effects in wild populations.

Principles and application of LIMS in mouse clinics - Holger Maier; Christine Schütt; Ralph Steinkamp; Anja Hurt; Elida Schneltzer; Philipp Gormanns; Christoph Lengger; Mark Griffiths; David Melvin; Neha Agrawal; Rafael Alcantara; Arthur Evans; et al. (Mammalian Genome, 2015)

Mouse large-scale phenotyping initiatives: overview of the European Mouse Disease Clinic (EUMODIC) and of the Wellcome Trust Sanger Institute Mouse Genetics Project - Abdel Ayadi; Marie-Christine Birling; Joanna Bottomley; James Bussell; Helmut Fuchs; Martin Fray; Valérie Gailus-Durner; Simon Greenaway; Richard Houghton; Natasha Karp; Sophie Leblanc; Christoph Lengger; et al. (Mammalian Genome, 2012)

Integration of Mouse Phenome Data Resources - John M. Hancock; Niels C. Adams; Vassilis Aidinis; Andrew Blake; Judith A. Blake; Molly Bogue; Steve D. M. Brown; Elissa J. Chesler; Duncan Davidson; Christopher Duran; Janan T. Eppig; Valérie Gailus-Durner; et al. (Mammalian Genome, 2008)